Basic Japanese grammar - Bleiler, Everett F. (Charles E. Tuttle, 1963)
The author has limited this book to modern colloquial Japanese, and does not overburden the student with literary language, rarely used alternate forms, unnecessary abrupt forms, causatives and direct conditions, and similar forms that night be required for a full knowledge of the writen language. It is the full idiomatic language, with thorough treatments of the material you really need: the noun, pronoun, adjective, demonstrative words, adverb, verb, negative forms, Chinese forms, courtesy and honorific forms, idiomatic constructions, word order, relationship of ideas, syntax.